Implementasi KPI Perusahaan: Kajian Literatur - Hasiholan Manurung; Humiras Hardi Purba (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2021)
Key performance indicators (KPI) are widely used in developing and advanced corporate systems. KPIs are used to measure the basic parameters that characterize organizational functions. Measurement of production efficiency regardless of the choice of optimization method, a key element of the author's methodology in designing a production system. Key performance indicators (KPIs) are commonly used in industry to support decision making and prioritize work across portfolios. KPI has a very objective assessment related to recommendations for decisions that must be taken in advancing the organization in order to achieve the goals outlined in the previous section and successfully inform. The method used in this paper is to review articles from various scientific articles from 2018-2020 using the keyword